ASSESSMENT OF PROPRIOCEPTIVE SENSITIVITY OF YOUNG SKI JUMPERS - Fendel, T.V.; Zubkov, D.A.; Savelyeva, A.N. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to evaluate the proprioceptive sensitivity of young ski jumpers. Methods and structure of the study. The study involved young ski jumpers aged 9 to 11 from Belarus, Slovakia and Russia. The sample consisted of 50 subjects, of which 19 were girls and 31 were boys. The main research methods were the method of pedagogical observation and the method of strain measurement. Results and conclusions. In the course of pedagogical observation, it was found that the most common mistakes in taking the acceleration stance are caused by uneven distribution of body weight, leading to critical changes in the general center of mass of athletes. Minimization of the asymmetry index when performing a vertical jump on a tensometric platform is one of the indicators of the quality of the functioning of the "posture-voluntary movements" system, as well as proprioceptive sensitivity in young ski jumpers.